The gross anatomy course: SARS-CoV-2 pandemic-related effects on students' learning, interest in peer-teaching, and students' perception of its importance. - Messerer, David Alexander Christian; Behr, Jonathan Lukas; Kraft, Sophie Felice; Schön, Michael; Horneffer, Astrid; Kühl, Susanne Julia; Benedikt Seifert, Lukas; Huber-Lang, Markus; Böckers, Tobias Maria; Böckers, Anja (Anatomical Sciences Education, 2023)
The COVID-19 pandemic required adjustments and limitations in university teaching, thereby challenging teaching concepts in anatomy requiring in-person contact, including the gross anatomy course. Therefore, the present study investigates the impact of COVID-19-associated adjustments on students' perception of the gross anatomy course's importance and quality, students' preferred learning setting and outcome, and their motivation to involve themselves in academic activities, including becoming a future peer-teacher of the course. Using paper-based questionnaires in Ulm, Germany, 397 (response rate: 82.3%) students of the winter term of 2020/2021 were surveyed using quantitative and qualitative items, which were compared with cohorts prior to the pandemic. Students reported a higher global rating on course quality during COVID-19 (pre-COVID-19: 5.3 ± 0.9, during-COVID-19: 5.6 ± 0.7, p < 0.001; 1 = very bad, 6 = very good). Students' perceived importance of the gross anatomy course showed a small but significant increase (pre-COVID-19: 4.2 ± 0.6, during-COVID-19: 4.3 ± 0.6, p < 0.001; 1 = strongly disagree, 6 = strongly agree). Students' motivation to apply as a peer-teacher remained stable, nevertheless, they reported less interest in transferring their knowledge to junior students. Finally, students reported that they spent significantly more learning time alone and their examination grades remained unchanged during the pandemic. Astonishingly, despite radical changes of the teaching environment due to COVID-19, students appreciate the offered teaching and highly valued the gross anatomy course.
EVALuna2:518007